Vaclovas Biržiška - lietuvių bibliotekininkystės terminijos pradininkas - Dubauskas, Stanislovas (Knygotyra, 1997)
The article deals with the librarianship terms used in V. Biržiška's book "About Books and Bookstores," published in 1918, Voronezh. The terms are grouped into clusters related to book collection, cataloguing, library classification, and others. The novelty and originality of these terms are revealed. The main term, "bookstore," is analyzed in detail, with each aspect of it being disclosed.